2014
DOI: 10.5688/ajpe7810190
|View full text |Cite
|
Sign up to set email alerts
|

An Eight-year Retrospective Study in “Flipped” Pharmacokinetics Courses

Abstract: Objective. To assess the impact on student performance of increased active learning strategies in a foundational pharmacokinetics course and a clinical pharmacokinetics course over an 8-year period. Design. A foundational pharmacokinetics course with a lecture-with-active-learning (LAL) format was redesigned to a recitation-format (REC) using smaller groups of students (ie, the class divided into thirds) and eventually to a team-based learning (TBL) format. The lecture-based clinical pharmacokinetics course wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
(16 reference statements)
4
32
0
Order By: Relevance
“…20 A growing body of literature on flipped classroom in medical, nursing, and pharmacy education reports that flipped courses improves attendance 21,22 and increases grades [21][22][23][24][25][26][27] and performance in follow-up courses. 28 Conversely, some reports discuss decreased student satisfaction, 25 significantly decreased examination scores resulting from a lack of accountability for out-of-class preparation, 29 and student satisfaction being influenced by the quality of content and activities. 27 Some negative aspects of TBL in the literature include increased preparation time by students and faculty members as well as student dissatisfaction (especially among introverted individuals and those who prefer the traditional faculty role of lecturing and storytelling).…”
Section: Introductionmentioning
confidence: 99%
“…20 A growing body of literature on flipped classroom in medical, nursing, and pharmacy education reports that flipped courses improves attendance 21,22 and increases grades [21][22][23][24][25][26][27] and performance in follow-up courses. 28 Conversely, some reports discuss decreased student satisfaction, 25 significantly decreased examination scores resulting from a lack of accountability for out-of-class preparation, 29 and student satisfaction being influenced by the quality of content and activities. 27 Some negative aspects of TBL in the literature include increased preparation time by students and faculty members as well as student dissatisfaction (especially among introverted individuals and those who prefer the traditional faculty role of lecturing and storytelling).…”
Section: Introductionmentioning
confidence: 99%
“…While there was, and still remains, some student resistance to the active learning, the student evaluations improved with the active learning sessions compared to the class years before the recitations were started. This is not always the case 21 , but for those who pursue active learning, it is an increase in student knowledge, not satisfaction, that is the primary objective.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the A J P E A c c e p t e d D r a f t recitation sessions, students were challenged to evaluate, apply, and think critically about course content in comparison to the pre-recitation years. While we do not have a stand-alone advanced pharmacology course to directly compare to, Persky and Dupuis found that by forcing students to apply knowledge to different situations in a foundational course improved their performance in a clinical pharmacokinetics course 21 and it is our belief that a similar increase in performance in our integrated therapeutics courses may also occur, but believe too many other variable exist (different instructors, course assessment changes, etc…) to make a conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcomes can be challenging as they may decrease in active learning environments even as performance increases. 11 Confidence judgments are complex and may not represent actual knowledge. 12 Clinical performance is the most relevant measure but it is challenging to link a single curricular intervention (ie, course change, active learning strategy) to the outcome (ie, advanced pharmacy practice experience (APPE) grade).…”
mentioning
confidence: 99%